2014
DOI: 10.6026/97320630010115
|View full text |Cite
|
Sign up to set email alerts
|

Computer Aided Screening of Phytochemicals from Garcinia against the Dengue NS2B/NS3 Protease

Abstract: Dengue virus NS2/NS3 protease because of its ability to cleave viral proteins is considered as an attractive target to screen antiviral agents. Medicinal plants contain a variety of phytochemicals that can be used as drug against different diseases and infections. Therefore, this study was designed to uncover possible phytochemical of different classes (Aromatic, Carbohydrates, Lignin, Saponins, Steroids, Tannins, Terpenoids, Xanthones) that could be used as inhibitors against the NS2B/NS3 protease of DENV. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
2
12
1
Order By: Relevance
“…Docking analysis provided various designs that were scored to decide ideal restricting modes. We found very high scores of docking than previously reported data [ 26 ]. Docking analysis contributed towards basic idea and binding energy values for each ligand.…”
Section: Discussioncontrasting
confidence: 61%
“…Docking analysis provided various designs that were scored to decide ideal restricting modes. We found very high scores of docking than previously reported data [ 26 ]. Docking analysis contributed towards basic idea and binding energy values for each ligand.…”
Section: Discussioncontrasting
confidence: 61%
“…The analysis has revealed 24 compounds that docked strongly to dengue virus NS2B-NS3 protease ( E dock < -130 kJ/mol) but not as strongly with mammalian trypsin, 21 compounds that docked strongly to the ATP binding site of DENV NS3 helicase ( E dock < -140 kJ/mol), 13 compounds that docked strongly to DENV methyltransferase ( E dock < -130 kJ/mol) but not as strongly with human RNA methyltransferase, 8 phytochemicals that showed notable docking to DENV RNA-dependent RNA polymerase, and 32 compounds that showed excellent docking properties with the hydrophobic pore of DENV envelope protein. The results of this study mirror previous docking studies that showed polyphenolic phytochemicals to be excellent docking ligands to dengue protein targets [42, 43, 46, 61]. These results and the current study underscore the importance of natural products from higher plants in drug discovery and may provide potential avenues for development of chemotherapeutic agents for the treatment of dengue fever.…”
Section: Discussionsupporting
confidence: 88%
“…and C 29 H 25 N 3 O 4 S, CID 54710332; Figure 1) and Ile165 were also reported by Salaemae et al [63] as determinants of binding with the substrate in the active site of the dengue virus NS3 protease, as was also noted by other authors [35,64,65].…”
supporting
confidence: 78%